Transformasi Desain Mihrab dalam Arsitektur Masjid Kontemporer di Era Modern: Kajian Literatur - Sania Rizqiatur Rohmah; Ai'datus Safitri; Vonny Aurellya Pratama (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study examines the transformation of mihrab design in contemporary mosque architecture in the modern era through a literature review approach. The mihrab, as an essential element in mosque architecture that marks the direction of the qibla, has undergone significant evolution in its design and application alongside the development of contemporary architecture. Using a descriptive qualitative research method, this study analyzes various sources of literature related to the development of mihrab design, including academic journals, books, and architectural documents. The findings of the study reveal that the transformation of mihrab design not only involves visual changes but also a reinterpretation of deeper symbolic and philosophical meanings. While there are views questioning the compatibility of contemporary designs with Islamic values, this study finds that innovations in mihrab design enrich the architectural heritage of Islam by creating a new visual language that still honors its essential function as a marker of the qibla direction. This research contributes to understanding how Islamic architecture can adapt to modernity while preserving its spiritual values.